2021
DOI: 10.3389/fmicb.2021.694161
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Quorum-Quenching Mechanism in Pseudomonas nitroreducens W-7 and Its Potential to Attenuate the Virulence of Dickeya zeae EC1

Abstract: Quorum quenching (QQ) is a novel, promising strategy that opens up a new perspective for controlling quorum-sensing (QS)-mediated bacterial pathogens. QQ is performed by interfering with population-sensing systems, such as by the inhibition of signal synthesis, catalysis of degrading enzymes, and modification of signals. In many Gram-negative pathogenic bacteria, a class of chemically conserved signaling molecules named N-acyl homoserine lactones (AHLs) have been widely studied. AHLs are involved in the modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Here, we used a highly active and stable AHL lactonase (PPH-G55V) [53] to test these effects. Our results suggest a new function for bacterial AHL lactonases, with a hydrolytic mechanism, thus far known to degrade mainly bacterial AHLs, QS signaling molecules and act as quorum-quenching enzymes that reduce virulence plant pathogens [27,32,33,69,70]. Patulin is a lactone-based fungal mycotoxin, shown to be related to pathogenicity affecting mycelium growth, and linked to host-pathogen-microbe interaction [58,[71][72][73].…”
Section: Discussionmentioning
confidence: 89%
“…Here, we used a highly active and stable AHL lactonase (PPH-G55V) [53] to test these effects. Our results suggest a new function for bacterial AHL lactonases, with a hydrolytic mechanism, thus far known to degrade mainly bacterial AHLs, QS signaling molecules and act as quorum-quenching enzymes that reduce virulence plant pathogens [27,32,33,69,70]. Patulin is a lactone-based fungal mycotoxin, shown to be related to pathogenicity affecting mycelium growth, and linked to host-pathogen-microbe interaction [58,[71][72][73].…”
Section: Discussionmentioning
confidence: 89%
“…Hence, disruption of S. mutans QS system has been proposed as a new anti-biofilm infection approach. Using QQ is considered to be one of the most promising methods for disrupting the QS systems and attenuating bacterial virulence [ 60 , 61 ]. As Mion et al [ 60 ] reported, QQ not only constitutes an interesting therapeutic strategy to fight against bacterial infections but also restricts the consequences of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…carotovovum in carrots, potatoes and Chinese cabbage [ 23 ]. Pseudomonas QQ-strains have also been recently used as biocontrol tools in agriculture [ 22 , 24 ], but this report shows its potential also in aquaculture. Overall, these results demonstrate the potential effectiveness of using AHL degradation in the fight against vibriosis in aquaculture, as well as marine invertebrate microbiota as a source of bacteria with QQ activity.…”
Section: Discussionmentioning
confidence: 99%
“…strain and is expressed in the agricultural pathogen Erwinia carotovora that causes a decrease in the production of enzymatic activity, as well as an attenuation in its virulence [ 14 ]. Subsequently, many AHL-degrading enzymes have been identified, some of which have shown the potential to be used as biocontrol agents in aquaculture [ 15 , 16 , 17 , 18 ] and agriculture [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%